Superconductivity in the t-J model - Plakida, N.M. (Condensed Matter Physics, 2002)
A comparison of microscopic theories for superconductivity in the limit of
strong electron correlations is presented. We consider the results for the
two-dimensional t-J model obtained within a projection technique for the
Green functions in terms of the Hubbard operators and a slave-fermion
representation for the RVB state. It is argued that the latter approach resulting
in an odd-symmetry p-wave pairing for fermions is inadequate. Представлено порівняння мікроскопічних теорій для надпровідності в границі сильних електронних кореляцій. Ми розглядаємо результати для двовимірної t-J моделі, отриманої в рамках методу проектування для функцій Гріна на мові операторів Габбарда, а також представленні допоміжних ферміонів для стану резонуючих валентних зв’язків. Стверджується, що останнє наближення, яке приводить до непарної симетрії p-хвильового спарювання для ферміонів є непридатним.